2002
DOI: 10.1074/jbc.m208506200
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in Human Nonmuscle Myosin IIA Found in Patients with May-Hegglin Anomaly and Fechtner Syndrome Result in Impaired Enzymatic Function

Abstract: A family of autosomal-dominant diseases including May-Hegglin anomaly, Fechtner syndrome, Sebastian syndrome, Alport syndrome, and Epstein syndrome are commonly characterized by giant platelets and thrombocytopenia. In addition, there may be leukocyte inclusions, deafness, cataracts, and nephritis, depending on the syndrome. Mutations in the human nonmuscle myosin IIA heavy chain gene (MYH9) have been linked to these diseases. Two of the recently described mutations, N93K and R702C, are conserved in smooth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 29 publications
(25 reference statements)
4
89
0
1
Order By: Relevance
“…The R702C and R709C mutants of human non-muscle myosin IIA and myosin IIB show ∼20% of the maximum actinactivated ATPase activity of wt and have a higher affinity for actin in the presence of ATP (its K m value is less than one-third that of wt) owing to the very slow release of ADP (Kim et al, 2005). Moreover, the motilities of the mutant myosins are severely impaired (Hu et al, 2002;Kim et al, 2005). The local concentration of the corresponding Myo3-R694C mutant in the ring was 1.8-fold higher than that of wt (Fig.…”
Section: Myo3 Gradually Accumulates On F-actin In the Contractile Ringmentioning
confidence: 99%
“…The R702C and R709C mutants of human non-muscle myosin IIA and myosin IIB show ∼20% of the maximum actinactivated ATPase activity of wt and have a higher affinity for actin in the presence of ATP (its K m value is less than one-third that of wt) owing to the very slow release of ADP (Kim et al, 2005). Moreover, the motilities of the mutant myosins are severely impaired (Hu et al, 2002;Kim et al, 2005). The local concentration of the corresponding Myo3-R694C mutant in the ring was 1.8-fold higher than that of wt (Fig.…”
Section: Myo3 Gradually Accumulates On F-actin In the Contractile Ringmentioning
confidence: 99%
“…These mutant NM IIs are impaired in their enzymatic activity and ability to translocate actin filaments in an in vitro motility assay, although both mutants can bind to actin and are released by ATP (41,42). Furthermore, these mutations have been shown to cause defects in humans (43) and in mice (44).…”
Section: Nm Ii-a or Nm Ii-b Modulates Egfr-dependent Downstreammentioning
confidence: 99%
“…20 As an abundant motor protein within MKs and the only representative of its family, 21 myosin-IIA is a good candidate mediator of proplatelet extension or platelet release. Biochemical studies suggest that certain N-terminal mutations found in patients with MYH9-related disorders reduce intrinsic ATPase activity, 22 whereas other common C-terminal mutations may compromise myosin filament formation. 23 Although both classes of mutations may interfere with myosin-IIA function, it is unclear whether monoallelic MYH9 mutations produce clinical phenotypes as a result of haploinsufficiency or dominant-negative effects.…”
Section: Introductionmentioning
confidence: 99%